Varmblodiga ridhästars inhysning i svenska avels- och uppfödningsverksamheter - Häggmar, Moa; Svensson, Miriam (2020)
Young riding horses should be able to move freely in large areas when growing up to develop a sustainable body for the future. The Swedish breed warm blooded riding horses are seen as healthy and durable in the sport. The structure of Swedish breeders back to 25 years ago is well known. However, their choice of housing system of young riding horses has not been investigated. Therefore, the aim was to identify and investigate today’s structure of Swedish breeders and their choice of housing system for young and growing horses. This work can be a basis for future investigations of housing system for young horses and the young horses’ future health. Further, this work can be used in education for Swedish breeders in housing systems for young horses. Three questions were answered in this essay: How has the structure of Swedish breeders changed over the last 25 years? How do the Swedish breeders choose a housing system for their youngster looks and how do the access to outdoor living look for Swedish breed young horses? This essay is based on a survey sent to breeders of Swedish warm blooded riding horses. The survey contained 22 questions of different character. The questions were chosen according to breeders, housing of horses, outdoor living for youngsters and marketing. For statistical analysis Microsoft Excel 2019 and chi2-test was used. The result showed that 79% of Swedish breeders were women and the majority were in the age 31 to 50 years. Most of the breeders, independent of age, had learned about breeding from friends. According to the answers of the survey breeders in the age group 31-60 years often used individual housing in stable. Individual housing in stable was also the choose for majority of the men and for breeders in the northern and the west part of Sweden. In the summer, 85% of the breeders had their horses out in pasture and kept in groups of two to four and five to eight horses. Availability of free movement and social contact among horses were the most important criteria for the breeders choose of housing system for young horses. The structure of Swedish breeders for warm blooded riding horses was similar to the structures of 1995 and 2010. Women in middle age (31-50 years and 51-60 years) is dominating the Swedish breeding meanwhile the men become fewer and older. Half of the Swedish breeders are housing their young horses in loose housing systems in the winter. In summertime four out of five breeders had their young horses out in pasture. In summertime, the horses were placed in pastures with a size of most commonly three to five hectares. In the winter, the horses were placed in paddocks with a size of most commonly one to two hectares. All the time during outdoor living the horses had social contact with other conspecifics.